The Effectiveness of a Hospital-Based School Liaison Program: A Comparative Study of Parental Perception of School Supports for Children With Pediatric Cancer and Neurofibromatosis Type 1. (July 2018) - Northman, Lisa; Morris, Marybeth; Loucas, Caitlyn; Ross, Sarah; Muriel, Anna C.; Guo, Dongjing; London, Wendy B.; Manley, Peter; Ullrich, Nicole J.
Childhood survivors of central nervous system (CNS) cancers (defined as cancers whose diagnosis or treatment affect the CNS) are at increased risk for educational related difficulties, as are children affected by neurofibromatosis type 1. This study evaluated the effectiveness of and satisfaction with a model of psychoeducation, consultation, and advocacy provided by a School Liaison Program (SLP) for families and schools of children with CNS-involved cancers compared with a control group of parents of children with a diagnosis of neurofibromatosis type 1 who did not receive school-based services. Results indicated significant between-group differences in parents' belief that their child is meeting academic potential, with parents who received SLP services reporting greater satisfaction with their child's progress, better understanding of their child's learning needs, and an increased ability to access school supports. The strong, positive impact associated with the consultation, psychoeducation, and parental advocacy training provided by the SLP suggests that a similar model of care would potentially benefit other groups of children whose neurocognitive functioning is compromised by chronic medical conditions.